Tree Cover of Haryana - Sapra, R. K. (Indian Forester, 2000)
Haryana is predominantly an agricultural State which has made tremendous strides in the field of social forestry. To quantify its achievements, Forest Survey of India undertook inventory survey in all the districts of the State. The sampling design followed was a two stage stratified random sampling and survey was done in 241 villages. Acacia nilotica, Eucalyptus and Dalbergia sissoo constitute more than 70% of growing stock of the State. More than 50% of growing stock has heen raised by individuals on farmlands. Among the strip forests, roads are best managed, while strips along railway lines are poorly stocked. The Northern region of the State is dynamic in forestry activities due to fertile plains coupled with more rainfall. The tree cover is more than four times of forest cover of the State. It is estimated that 8.6% of geographical area of State is bearing forest/tree cover which has not only reduced the pressure on natural forests, but also increased the employment opportunities leading to income generation in rural areas.